2012
DOI: 10.1097/ccm.0b013e3182657b75
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusions are associated with lower mortality in patients with severe sepsis and septic shock

Abstract: In this observational study of patients with community-acquired severe sepsis and septic shock, red blood cell transfusions were associated with lower risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 22 publications
5
51
1
6
Order By: Relevance
“…The propensity score-matched approach is a powerful tool that attempts to construct a randomised experiment-like situation by comparing groups with similar observed characteristics, without specifying the relationships between confounders and outcomes. Although analysis of the baseline patient characteristics in the unmatched group showed more corticosteroid use in patients with more severe illness, one-to-one propensity score matching successfully balanced the characteristics between patient groups with and without corticosteroid use, including factors that have the potential to affect mortality or are known to affect mortality in patients with pneumonia, as described in the methods section [1,3,30,[35][36][37][38][39]. Our results suggest that patients with severe CAP and shock who received corticosteroids were less likely to die than similar patients who did not receive corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propensity score-matched approach is a powerful tool that attempts to construct a randomised experiment-like situation by comparing groups with similar observed characteristics, without specifying the relationships between confounders and outcomes. Although analysis of the baseline patient characteristics in the unmatched group showed more corticosteroid use in patients with more severe illness, one-to-one propensity score matching successfully balanced the characteristics between patient groups with and without corticosteroid use, including factors that have the potential to affect mortality or are known to affect mortality in patients with pneumonia, as described in the methods section [1,3,30,[35][36][37][38][39]. Our results suggest that patients with severe CAP and shock who received corticosteroids were less likely to die than similar patients who did not receive corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the propensity score, we fitted a logistic regression model for corticosteroid use as a function of patient and hospital factors including: age; sex; hospital type (academic or nonacademic) and hospital volume; JCS score; liver cirrhosis with a Child-Pugh score of 10-15 (Class C); coexisting lung disease (asthma or chronic obstructive pulmonary disease); evidence of pleural effusion with/without paracentesis or drainage; evidence of gastrointestinal ulcer bleeding; gastroscopy with/without a haemostatic procedure; intermittent haemodialysis and continuous renal replacement therapy after admission; type of catecholamine used (dopamine, dobutamine or noradrenaline); blood transfusion use; albumin use; antithrombin concentration use; nonsteroidal anti-inflammatory drug use; intravenous immunoglobulin use; sivelestat sodium use; initial use of two or more antibiotics; and each type of antibiotic used [1,3,27,30,[35][36][37][38][39]. The C-statistic was used to evaluate the goodness of fit.…”
Section: Discussionmentioning
confidence: 99%
“…1). Likewise, Park and colleagues [16] reported that RBC transfusion was associated with a lower risk of mortality in patients with severe sepsis. Fig.…”
Section: What Is the Evidence?mentioning
confidence: 95%
“…Algunas guías de práctica clínica sobre alternativas a la transfusión también han considerado esta medida como de gran eficacia para disminuir las necesidades de transfusión alogénica 16,17 . Sin embargo, durante estos últimos años, diferentes estudios han encontrado que la transfusión de sangre alogénica reduce la mortalidad y proporciona mayores tasas de supervivencia a los 30 días en grupos de pacientes concretos: pacientes con sepsis grave 18 , pacientes críticos de 66 a 80 años intervenidos de cirugía no cardiovascular 19 , y pacientes con sepsis grave por neumonía adquirida en la comunidad 20 . Este hallazgo podría ser particularmente cierto en los pacientes sépticos, pero podría aplicarse por igual a todos los pacientes en estado crítico 21,22 .…”
Section: Punto De Partidaunclassified